Protein and Mineral Compositions of Some Local Fishes of Tripura, India - DEBNATH, CHANDAN; SAHOO, LOPAMUDRA; SINGHA, ABHIJIT; YADAV, GULAB SINGH; DATTA, M.; NGACHAN, S.V. (Indian Journal of Hill Farming, 2015)
In this study, eight fish species namely, A. mola, E. danricus, P. sophore, C. fasciata, L. bata, C. catla, L. rohita and C. mrigala from Tripura were analyzed for protein and mineral compositionsin their dried form as limited study is available in this line. The specimens were collected live, processed and oven-dried before analysing them in triplicate using standard procedures. Allfishes irrespective of major, medium and small indigenous species were found nutritive even in their dried state. Protein and mineral contents showed significant variations among the species. Protein content varied from 39.37% (C. lalia) to 75.43% (L. bata). Phosphorus content varied from 0.09% (P. sophore) to 0.54% (C. fasciata), potassium from 0.28% (C. fasciata) to 0.95% (P. sophore) and calcium from 0.06% (Labeo species) to 1.66% (C. fasciata). Copper content was found from 16.1 mg/kg (P. sophore) to 273.9 mg/kg (C. mrigala), zinc from 23.5 mg/kg (L. rohita) to 154.4 mg/kg (E. danricus), iron from 91.8 mg/kg (C. catla) to 997.7 mg/kg (C. fasciata) and manganese from 3.9 mg/kg (L. rohita) to 51.4 mg/kg (C. fasciata). Moisturecontent was the highest in C. fasciata (14.17%) whereas, L. bata and C. catla showed the least amount (11.17%).